2011
DOI: 10.1007/s10562-011-0699-7
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Amination of Triacetoneamine with n-Butylamine Over Cu–Cr–La/γ-Al2O3

Abstract: A series of Cu-based catalysts were prepared and examined for the reductive amination of triacetoneamine with n-butylamine, thereinto, Cu-Cr-La/c-Al 2 O 3 showed excellent results. The catalysts were studied by XRD, XPS, H 2 -TPR and NH 3 -TPD. It was found that doped Cr remarkably enhanced the activity of Cu/c-Al 2 O 3 due to better dispersion of Cu 0 , which is believed to be the active site for the reductive amination. Additionally, it was obvious that introduction of La to Cu-Cr/c-Al 2 O 3 led to a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…It was found that Cu-Cr-La/γ-Al 2 O 3 displayed the best catalytic performance, which was accordance with the results Sun et al reported 20 (Sun et al, 2011), so this catalyst was used for the following research.…”
Section: Catalyst Selectionsupporting
confidence: 87%
“…It was found that Cu-Cr-La/γ-Al 2 O 3 displayed the best catalytic performance, which was accordance with the results Sun et al reported 20 (Sun et al, 2011), so this catalyst was used for the following research.…”
Section: Catalyst Selectionsupporting
confidence: 87%
“…Catalyst selection Although our previous work had shown Cu-Cr-La/c-Al 2 O 3 to be an effective catalyst for reductive amination of alcohols, aldehydes, and ketones [20][21][22], the catalyst had to be optimized for this reaction system. This was achieved by varying the amount of La in the catalyst; the results are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 932.59 eV can be assigned to the binding energy of the Cu 0 species at the Cu2p3/2 level. Therefore, it is likely that the co-production process proceeds smoothly because the copper is sufficiently active for reductive amination of alcohols [20][21][22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations